The effects of the extraction of non-ferrous metals on the ichthiofauna of the Lapus river bassin - Gavril, Ardelean; Wilhelm, Sándor (Acta Agraria Debreceniensis, 2007)
Over the period 2003-2005 we made ichthyologic research in the basin of the Lapus river. During the sampling we noticed that in some area the water was polluted. In those areas fishweretotallyorpartiallymissing.The main pollution sources are those related to nonferrous metal extraction and processing, but there is also pollution from organic substances resulted from the communal residual waters, as well as the “tuica”(alcoholic drink) distilleries.Confronting the spots of the pollution sources with the results of the ichthyologic research.we noticed a significantcorrespondencebetween the qualitative and quantitative component of the ichthyofauna and the presence of these sources.We could, therefore prove the effect of the process of self-purificationofthewater,aswellastheexistenceofsomespeciesoffishshowing a great degree of tolerance towards pollution.